Personalising Learning in Teacher Education - Jones, Mellita (Springer Singapore, 2018)
This volume sheds light on debates about personalised learning in teacher education by exploring the popular emergence of personalising learning in education and hence its significance in teacher education in the 21st century. It examines personalising learning theory and explores the tenets of this theory and its recent trends in international settings. The theory is explored in relation to both general and higher education pedagogy, and in a range of examples within a teacher education context. The examples from practice provide insights into maximising the potential for personalising learning theory to enhance teaching, learning and assessment in teacher education. The book includes case studies involving pre-service teachers working in communities of practice with one another, with schools and with the wider community. Examples of technology for personalising learning are also described. All the case studies demonstrate how the learner is made central to the teaching and assessment approaches adopted and contributes to a lifelong learning continuum. Providing insights into a new pedagogy for teacher education that leads to an enriched student experience, the book presents a model for personalising learning in teacher education that offers support for 21st century teacher educators.